PROFESSIONAL TRAINING STANDARDS FOR BACHELOR’S DEGREE IN INTERNATIONAL RELATIONS: BRITISH EXPERIENCE (Comparative Professional Pedagogy, 2023)
This article justifies the relevance of studying the experience of the United Kingdom in the professional training of bachelors in International Relations.It is established that the professional functions and training of bachelors in International Relations are regulated by the provisions of the "National Occupational Standards" (NOS), which clearly outline the specific nature and professional functions of experts in the field of international relations. According to the provisions of the educational standard, the goal of professional training is to provide professional knowledge, skills, and abilities, fostering the development of professionally significant qualities of future bachelors through interdisciplinary knowledge. Future bachelors in International Relations should acquire subject knowledge, understanding, and skills. The content of program outcomes and the main requirements for the professional competence of bachelors in International Relations are determined. It is noted that adherence to scientifically substantiated content structuring requires compliance with the needs of the labor market, individual needs, and societal expectations; orientation towards the achievements of political science theory and practice; professional orientation; studying the best practices of renowned politicians; providing practical training and internships abroad; balancing theoretical and practical learning; flexible, variable, and modular structure of educational programs and curricula; adapting the educational program to the needs of students, institutions, and society.In general, the standard regulates a set of requirements for organizing the educational process; motivating educational institutions to use a wide range of intellectual, informational, technological, and material resources; providing students with broad and balanced knowledge, understanding of the fundamental features of political science education in an interdisciplinary context; encouraging students to participate in addressing key questions related to the goals, values, and outcomes of education; providing students with opportunities for planning individual educational trajectories and lifelong learning.
Keywords: United Kingdom; professional training; education standardization; bachelor’s degree; International Relations